Intrahost variation and evolutionary dynamics of adenoviruses correlate to neutrophils in infected patients. Issue 8 (11th April 2022) - Huo, Shuting; Hai, Yan; Guo, Yaxin; Nie, Li; Li, Hongmei; Qiao, Peiwen; Zong, Kexin; Li, Xin; Guo, Yuanyuan; Song, Jingdong; Zhao, Honglan; Lei, Wenwen; et al.
Abstract: With deep sequencing of virus genomes within the hosts, intrahost single nucleotide variations (iSNVs) have been used for analyses of virus genome variation and evolution, which is indicated to correlate with viral pathogenesis and disease severity. Little is known about the features of iSNVs among DNA viruses. We performed the epidemiological and laboratory investigation of one outbreak of adenovirus. The whole genomes of viruses in both original oral swabs and cell‐cultured virus isolates were deeply sequenced. We identified 737 iSNVs in the viral genomes sequenced from original samples and 46 viral iSNVs in cell‐cultured isolates, with 33 iSNVs shared by original samples and cultured isolates. Meanwhile, we found these 33 iSNVs were shared by different patients, among which, three hot spot areas 6367−6401, 9213−9247, and 10 584−10 606 within the functional genes of the adenovirus genome were found. Notably, the substitution rates of iSNVs were closely correlated with the clinical and immune indicators of the patients. Especially a positive correlation to neutrophils was found, indicating a predictable biomarker of iSNV dynamics. Our findings demonstrated the neutrophil‐correlated dynamic evolution features of the iSNVs within adenoviruses, which indicates a virus−host interaction during human infection of a DNA virus.